2012
DOI: 10.1007/s10147-012-0503-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for patients in postoperative brain metastases from surgically resected non-small cell lung cancer

Abstract: Our study found that the foregoing clinical characteristics in postoperative brain metastases and the administration of treatment contributed to patient life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 33 publications
5
17
0
Order By: Relevance
“…In addition, adenocarcinoma showed a longer disease-free interval and better postrecurrence survival than non-adenocarcinoma. The results agreed with other studies [7,8,[10][11][12].…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…In addition, adenocarcinoma showed a longer disease-free interval and better postrecurrence survival than non-adenocarcinoma. The results agreed with other studies [7,8,[10][11][12].…”
Section: Discussionsupporting
confidence: 95%
“…According to the report of Sakamoto et al, 6.7% (65/967) of lung cancer patients developed postoperative brain metastases, and 3.2% (31/967) of patients had only brain metastasis as the initial postoperative recurrence [7]. The postrecurrence survival of these patients also showed results to other reported studies.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…They can be detected up to 30% to 55% of the cases at autopsy (28). Sakamoto et al (29) reported that 3.2% of the patients will develop only metachronous brain metastasis after surgery for the primary tumor. The survival after recurrence is poor.…”
Section: Brain Metastasismentioning
confidence: 99%